Ansavaricins A–E: five new streptovaricin derivatives from Streptomyces sp. S012. Issue 10 (17th January 2017) - Zhang, Zhiqiang; Zhang, Juanli; Song, Rentai; Guo, Zhixing; Wang, Haoxin; Zhu, Jing; Lu, Chunhua; Shen, Yuemao
Abstract : Five new polyketides of the ansamycin class, named ansavaricins A–E (1–5 ), together with three known streptovaricins6–8, were isolated from the Streptomyces sp. S012 strain. Abstract : Five new polyketides of the ansamycin class, named ansavaricins A–E (1–5 ), together with three known streptovaricins6–8, were isolated from the Streptomyces sp. S012 strain. The structures of1–8 were determined by analysis of the 1D and 2D NMR spectroscopic and high-resolution ESIMS data, which showed plentiful structural variations in the naphthoquinoid moieties and ansa chains of ansavaricins A–E. Ansavaricins A–E showed almost no obvious toxicity to the test Gram positive and negative bacteria. However, compounds5, 6 and7 significantly inhibited the secretion of SPI-1 effectors of Salmonella enterica serovar Typhimurium, indicating a potential in the development of antivirulence antibacterial drugs.